(untitled) (Proceedings of the International Conference on Education, 2019)
Reading comprehension has been considered as a major issue in the Indonesian EFL context including in the junior high schools. Whereas in fact, Indonesian junior high school students have been asked by the Indonesian Ministry of Education and Culture to understand various English texts effectively. Therefore, in an attempt to comply with the required criteria above, this paper proposes a possible solution to cope with Indonesian students’ reading comprehension issue. In this sense, CIRC proposed as a possible technique to enhance Indonesian junior high school students’ reading comprehension. Specifically, this research attempts to measure the effectiveness of CIRC technique on students’ reading comprehension at grade seven of a junior school located in West Sumatera, Indonesia namely the MTsN Koto Baru Junior High School. Accordingly, the study employed a quasi-experimental design, comparing students’ pre-test and post-test scores to measure the effectiveness of CIRC towards students’ reading comprehension. The different result between the pre-test and post-test tested using the paired sample t-test. It was found that students’ scores on pre-test (before treatment) was lower than post-test (after treatment). Thus, it can be inferred that CIRC was effective to increase students’ reading comprehension. Keywords: Reading Comprehension, CIRC Technique